مدى رضي أخصائيات مراكز مصادر التعلم عن مراكزهن في المدارس الثانوية الحكومية بمدينة الرياض - القحطانى، رمش بنت ناصر سعد; العمرو، نهلة بنت عبدالله (جامعة سوهاج - كلية التربية, 2020)
هدفت الدراسة إلى التعرف على مدى رضى أخصائيات مراكز مصادر التعلم عن مراكزهن في المدارس الثانوية الحكومية بمدينة الرياض. واتبعت الدراسة المنهج الوصفي، واستخدمت استبانة مكونة من (53) عبارة موزعة على أربعة محاور، تم تحكيمها وقياس مدى صدقها وثباتها، وذلك قبل توزيعها على أفراد العينة التي اختيرت عشوائيا وبلغت (73) أخصائية مركز مصادر تعلم في المدارس الثانوية الحكومية للبنات بمدينة الرياض. وتوصلت الدراسة إلى أن درجة رضى أخصائيات مراكز مصادر التعلم عن مراكزهن في المدارس الثانوية الحكومية بمدينة الرياض جاءت بدرجة عالية. ومن أبرز المعوقات التي كشفت عنها الدراسة: عدم توفر صيانة دورية، تدني مستوى الدعم المادي، عدم توافر بعض الوسائل التعليمية في المركز، عدم بناء مرفق خاص مجهز بالمواصفات والشروط الأساسية للمركز، وتدني مستوى بعض الأجهزة المتوفرة في المركز. وأوصت الدراسة بما يلي: توفير مخصص مالي شاملة لجميع تكاليف المركز، توفير خدمة الأنترنت وأجهزة حاسب آلي تتناسب مع أعداد المستفيدين، العمل على تفريغ أخصائي المركز لعمل المركز، وتحفيزه ماديا ومعنويا، إقامة الدورات التدريبية اللازمة لأخصائي المراكز، وللمعلمين، وللطلبة، تخصيص حصة في الجدول الدراسي للاستفادة من خدمات مركز مصادر التعلم، زيادة وعي الإدارة المدرسية بضرورة تفعيل مركز مصادر التعلم، التعميم على كافة المدارس بضرورة تفعيل مراكز مصادر التعلم والرفع بالاحتياجات الضرورية بصفة مستمرة لوزارة التعليم.
This study aimed to identify the extent satisfaction of the female specialists of the learning resource centers about their centers in the governmental secondary schools in Riyadh. The study using the descriptive methodology, and create a questionnaire consisting of (53) phrases distributed in four axes, which was arbitrated and calculated validity before distributed to randomly selected members (73) female specialists of learning resource center specialists in governmental secondary schools in Riyadh. The results of the study: the degree of satisfaction of the female specialists of the learning resource centers about their centers in the governmental secondary schools in Riyadh was high. The main obstacles: the lack of periodic maintenance, low level of material support, some educational materials in the center was decreasing, don't has a special building equipped with the basic specifications and conditions of the center, and the level of some of the devices in the center was decreasing. The study recommended the following: Providing a financial allocation for all costs of the center, providing internet service and computers, working on emptying the specialist of center's for the work of the center, setting up the necessary training courses for the specialists of centers, teachers and students, allocating a time in Schedule to benefit from the learning resources center services. Increase the awareness of the administration of the need to activate the center.
Keywords: أخصائيو المعلومات -- الرضا الوظيفي -- المدارس الحكومية -- التعليم الثانوي -- السعودية